(3QhVI GdWGdHjf hYeOI GdeJbjfs - (3jMji Hf TQa Hf oepqQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf,J (B676 (3g` s ((3YHO Gddg Hf eMeO Hf MSjf s)
(3ChdgG (B:s
(3GdMeO ddg Pi GdLdGd hGdEcQGe , hGdaVd hGdWhd hGdeff GdLSGe , GdPi gOGfG ddESdGe , hGSHZ YdjfG s
(3BNQgG (B:s
(3BNQg ef HGH UObI GdJWhY (B" (3bhdg (B: (3hbGd (B: (3hYdi GdLedI GdCNP ai GdedG hJQc GdCNP ai GdNdG CMSf , Je HMeO Gddg hefg gPG GdLRA s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3jdjgG fSNI CNQi ef hQbI (B206 - 244 (3dYdgG GdcJGHs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B149 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B202s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdTGaYjs